ANALYSIS OF THE INFLUENCE OF RISK MANAGEMENT AND MONITORING ON THE EFFECTIVENESS OF BUDGET ABSORPTION IN THE PUBLIC WORKS AND SPATIAL PLANNING DEPARTMENT OF NORTH MINAHASA REGENCY - Hamka Prasetia Mamonto; Recky H. E. Sendouw; Steven V. Tarore (Journal of International Islamic Law, Human Right and Public Policy, 2026)
This study aims to analyze the effect of risk management and monitoring on the effectiveness of budget absorption at the Public Works and Spatial Planning Office of North Minahasa Regency. Specifically, this study aims to: (1) analyze the effect of risk management on the effectiveness of budget absorption, (2) analyze the effect of monitoring on the effectiveness of budget absorption, and (3) analyze the simultaneous effect of risk management and monitoring on the effectiveness of budget absorption. This study employs a quantitative approach using multiple linear regression analysis. The results show that partially, risk management has a positive and significant effect on the effectiveness of budget absorption, with a t-value of 4.743 and a significance level of 0.002. Monitoring also has a positive and significant effect, with a t-value of 3.842 and a significance level of 0.000. Simultaneously, risk management and monitoring have a significant effect on the effectiveness of budget absorption, with an F-value of 7.855 and a significance level of 0.001. The coefficient of determination (R²) is 0.282, indicating that both variables contribute 28.2% to the effectiveness of budget absorption. These findings indicate that the effective implementation of risk management and monitoring jointly enhances the effectiveness of budget absorption.